2023
DOI: 10.1177/19458924231163969
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Evaluation of COVID-19-Related Olfactory Dysfunction

Abstract: Background Olfactory dysfunction has been reported in 47.85% of COVID patients. It can be broadly categorized into conductive or sensorineural olfactory loss. Conductive loss occurs due to impaired nasal air flow, while sensorineural loss implies dysfunction of the olfactory epithelium or central olfactory pathways. Objectives The aim of this study was to analyze the clinical and imaging findings in patients with COVID-related olfactory dysfunction. Additionally, the study aimed to investigate the possible mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Additionally, we have investigated cognitive and mood deficits associated with post-COVID OD and possible available treatments. The MRI studies for COVID-19-related OD employed various methodologies, assessing structural and functional aspects of the olfactory system through various parameters [2,4,[34][35][36][37][38][39][40][41][44][45][46]. Evaluation of OBV and the OS depth, common parameters in different studies, revealed a consistent reduction in OBV and OS depth in post-COVID-19 patients with OD, suggesting direct damage to olfactory neural pathways [2,35,[37][38][39][40]44,46].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we have investigated cognitive and mood deficits associated with post-COVID OD and possible available treatments. The MRI studies for COVID-19-related OD employed various methodologies, assessing structural and functional aspects of the olfactory system through various parameters [2,4,[34][35][36][37][38][39][40][41][44][45][46]. Evaluation of OBV and the OS depth, common parameters in different studies, revealed a consistent reduction in OBV and OS depth in post-COVID-19 patients with OD, suggesting direct damage to olfactory neural pathways [2,35,[37][38][39][40]44,46].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…In fact, they found significant decreases in the values of both OBV and OS depth. Instead, Abdou et al [41], in a study that compared 110 patients with post-COVID-19 OD and a control group of 50 normal subjects, showed significantly increased OB dimensions (length × width × height) and volume compared with controls. They hypothesize that the mechanism underlying COVID-related OD is sensorineural loss through virus spread and damage to the OE and pathways.…”
Section: Obv and Os Depth Changesmentioning
confidence: 95%
“…OB is transmitting ascending olfactory sensation as well as mechanoceptive signal of rhythmic nasal airflow and is receiving “top-down” information related to olfactory processing (from ctx, HPC, Amygdala) as well as oscillatory drive (e.g. theta, gamma from HPC); reports of its possible COVID-19 inflammatory damage are not fully consistent (Sherif et al, 2022 ; Abdou et al, 2023 ; Muccioli et al, 2023 ). Piriform cortex is the primary target of the olfactory tract where cortical processing of olfactory information involves RRO-driven local gamma oscillations (Gonzalez et al, 2023 ) and is transmitted to other cortical structures, oscillatory coupled at different frequencies [including RRO (Mofleh and Kocsis, 2021a )], for further processing in the context of different cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory and taste dysfunction have been reported in up to 47% of COVID-19 patients [ 11 13 ]. Regarding the concern of COVID-19 affecting taste among the study population, this confounding factor was excluded.…”
mentioning
confidence: 99%